Stability in a Multi-Stage HIV Infection Model with General Incidence Rate (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we propose a multi-stage HIV infection model withgeneral incidence rate to describe the influence of raltegravir intensificationon viral dynamics. The basic reproduction number $R_0$ is established. Theinfection-free equilibrium $E_0$ is locally asymptotically stable if $R_0 1.$
Keywords: Multi-stage models; Lyapunov; incidence; stability.